Nafas face mask / Nadia Shamsul Aizat … [et al.] - Shamsul Aizat, Nadia; Ab Halim, Puteri Nur Najwa; Yusni, Siti Nur Khairunnisa; Mohd Zani, Siti Sarah; Wee, Hassnah (Faculty of Computer and Mathematical Sciences, 2022)
Because of the COVID-19 outbreak, everyone is required to wear a mask whenever they enter a public space; however, most people have difficulty breathing while wearing a mask, and some people may smell something foul behind the mask. The "Nafas face mask" is also a novel fabric mask with a fragrance filter. The word 'nafas' means 'breath' in Malay. The product's primary goal is to promote the use of face masks because some people, particularly children, refuse to wear them due to their unpleasant odour. Wearing a mask can be extremely uncomfortable for adults and children with sensory issues. They may be sensitive to the sensation, odour, or proximity of a mask. This 'Nafas face mask' is made of batik-patterned fabric and contains a fragrance-producing filter. This face mask is simple to apply and suitable for most people, especially those who have bad breath. Face masks are used as part of personal protective equipment and as a public health intervention to aid in the prevention of the COVID-19 virus's spread. This initiative helps to achieve the UN Sustainable Development Goals of Good Health and Well-Being (SDG3), Responsible Consumption and Production (SDG12), and Life on Land (SDG13) (SDG15). This product benefits society as a whole by improving people's quality of life and encouraging them to recycle fabric products to achieve a sustainable environment. It also has commercialization potential.